Benign rib tumors: a case series from tertiary care Centre of Nepal and review of literature. Issue 11 (29th November 2021) - Jaiswal, Lokesh Shekher; Neupane, Durga
Abstract: Rib tumors are rare. They can present with wide varieties of symptoms and differentiating benign from malignant lesions is challenging. A careful history and supporting investigations can help to reach the definite diagnosis. Surgical resection is the treatment of choice with excellent prognosis. A total of four patients were operated for the management of rib tumors over a period of 5 years at our institution. All four were benign lesions and included simple bone cyst, fibrous dysplasia with aneurysmal bone cyst, aneurysmal bone cyst and enchondroma. There were three male and one female. None of them is having recurrence till now. Surgical resection is the treatment of choice for benign rib tumors as it provides diagnostic and curative treatment.